Peran Media Audio-Visual dalam Mendukung Pembelajaran Bahasa Kedua Pada Konten ’Johny Johny Yes Papa’ - Susetya, Hemas Haryas Harja; Sukardi, Mochamad Ighfir; Lathifah, Warda (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study examines the impact of the Johny Johny Yes Papa song on YouTube on early childhood English vocabulary acquisition. The purpose of this research is to analyze vocabulary improvement through engaging audio-visual exposure. Using a descriptive qualitative approach, the study employs participant observation, parent interviews, and content analysis. The findings indicate that children who frequently watch this content are able to imitate words such as "yes," "no," "sugar," and "papa" and use these words in everyday contexts. Engaging visuals and repetition in the video help support vocabulary internalization. The study concludes that digital media like YouTube can effectively introduce a second language to young children through consistent exposure that aligns with their level of comprehension.